Tuftelin's involvement in embryonic development. Issue 5 (2nd May 2019) - Shilo, Dekel; Blumenfeld, Anat; Haze, Amir; Sharon, Shay; Goren, Koby; Hanhan, Salem; Gruenbaum‐Cohen, Yael; Ornoy, Asher; Deutsch, Dan
Abstract: Little is known about tuftelin expression in the developing embryo, previously it was thought to play a role in tooth enamel mineralization. In this study we show tuftelin's spatio‐temporal expression in mineralizing and nonmineralizing tissues of the craniofacial complex in the developing mouse embryo. Embryos aged E10.5−E18.5 and newborns aged P3 were used in this study. Polymerase chain reaction (PCR), Real‐time PCR, sequencing, and in‐situ hybridization were used to detect and quantify messenger RNA (mRNA) expression in different developmental stages. We applied indirect immunohistochemistry and western‐blot analyses to investigate protein expression. Two tuftelin mRNA transcripts and a single 64KDa protein were detected throughout embryonic development. Tuftelin was detected in tissues which develop from different embryonic origins; ectoderm, ectomesenchyme, and mesoderm. Tuftelin mRNA and protein were expressed already at E10.5, before the initiation of tooth formation and earlier than previously described. The expression pattern of tuftelin mRNA and protein exhibits dynamic spatio‐temporal changes in various tissues. Tuftelin is expressed in neuronal tissues, thus fitting with its described correlation to nerve growth factor. A shift between cytoplasmatic and perinuclear/nuclear expression implies a possible role in regulation of transcription. Recent studies showed tuftelin is induced under hypoxic conditions in‐vitro and in‐vivo, through the hypoxia‐inducible factor 1‐α pathway. These results led to the hypothesis that tuftelin is involved in adaptation to hypoxic conditions. The fact that much of mammalian embryogenesis occurs at O2 concentrations of 1–5%, raises the possibility that tuftelin expression throughout development is due to its role in the adaptive mechanisms in response to hypoxia. Abstract : Tuftelin expression during mouse embryonic development in bone, cartilage, eye, brain, trigeminal ganglion and tooth germ. HIGHLIGHTS: Tuftelin was detected in ectodermal, ectomesenchymal and mesodermal tissues. Shift between cytoplasmatic and perinuclear/nuclear expression implies possible regulation of transcription. Tuftelin expression throughout development might be due to its role in the adaptive mechanisms in response to hypoxia.